2017
DOI: 10.1039/c7ra01429e
|View full text |Cite
|
Sign up to set email alerts
|

Effect of copper oxide shell thickness on flash light sintering of copper nanoparticle ink

Abstract: In this study, the effect of the thickness of a copper oxide-shell on flash light sintering of Cu nanoparticles (NPs) was investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…For inkjet printing, conductive inks based on silver [14][15][16][17][18][19][20] and copper [21][22][23][24][25] have been widely studied. Copper ink has received considerable attentions because of its relative high electrical conductivity and very low cost [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…For inkjet printing, conductive inks based on silver [14][15][16][17][18][19][20] and copper [21][22][23][24][25] have been widely studied. Copper ink has received considerable attentions because of its relative high electrical conductivity and very low cost [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Cu oxide nanoparticles are more stable than their Cu nanoparticle counterparts. The IPL sintering can remove the oxide shells of Cu nanoparticles using the IPL-reactive protective agents, such as PVP, leaving a conductive Cu film in a short period of time (a few ms) under ambient conditions [ 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 ]. Ryu et al explained this phenomenon by oxide reduction either via an intermediate acid created by light irradiation or by hydroxyl (–OH) end groups, which act like long-chain alcohol reductants [ 100 ] ( Figure 11 ).…”
Section: Surface Designs By Surface Protective Layers Against the mentioning
confidence: 99%
“…Oh et al reported the systematic investigation on the effect of Cu oxide shell thickness on the IPL sintering of PVP-protected Cu nanoparticle ink [ 104 ]. They prepared the Cu nanoparticles with different thicknesses of the Cu oxide shell, from 2.1 to 14 nm, by increasing the oxidation temperatures from 100 to 500 °C in the air.…”
Section: Surface Designs By Surface Protective Layers Against the mentioning
confidence: 99%
See 1 more Smart Citation
“…To resolve these issues, various research efforts have utilized alternative methods such as laser, microwave, and light sintering processes. The flash light sintering method has been studied since it can dramatically decrease the total process time to a few seconds when it sinters metals such as Cu and Ag under standard pressure and temperature conditions [28][29][30][31]. However, studies on the flash light sintering of ceramic materials is relatively insufficient.…”
Section: Introductionmentioning
confidence: 99%